The influence of think pair share (TPS) learning model on fifth- grade students’ learning outcomes of civic education - Hidayanti, Mifta; Abdullah, Kusmajid (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2023)
This study aims to determine the influence of the think pair share (TPS) learning model on the learning outcomes of civic education on fifth grade class student in elementary school at Jakarta Timur Cilangkap. The subject of this research is fourth-grade students with instrument pre-test and post-test of Civic Education subject. While the research method used is a quantitative research method with a Quasi- Experimental Design research design. The type of sample used was Non-Probability Sampling with a total of 60 participants divide into 2 class which is 30 at experimental class and 30 in a control class. From the results of the calculation of the t test in the study, it obtained a value of t count = 2,4704 ≥ t table 2.000 which stated that there was a significant effect of learning using the think pair learning model on civic education learning outcomes in one of the elementary schools at Jakarta Timur Colangkap. The think pair learning model applied by teaching staff to their students can increase the level of creativity and courage of a student so that students can learn effectively and have fun, especially in this study the subjects taken were civic education.